2020
DOI: 10.1055/s-0040-1702942
|View full text |Cite
|
Sign up to set email alerts
|

Review on the Diagnosis and Treatment of Reversible Cerebral Vasoconstriction Syndrome in Children and Adolescents

Abstract: Reversible cerebral vasoconstriction syndrome (RCVS) is a clinical–radiologic diagnosis that affects children and adolescents, but it is much more frequently reported in adults. Clinically, patients present with severe and commonly recurrent thunderclap headaches. Typical precipitating triggers include vasoactive substances, serotonergic agents, and the postpartum period. There may be associated neurologic complications at presentation or in the weeks following, such as convexity subarachnoid hemorrhage, strok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 45 publications
0
14
1
Order By: Relevance
“…2,3,5,6 It has also been associated with sympathomimetic medication and immunosuppression. 1 In our case, though, no trigger was identified.…”
Section: Discussioncontrasting
confidence: 51%
“…2,3,5,6 It has also been associated with sympathomimetic medication and immunosuppression. 1 In our case, though, no trigger was identified.…”
Section: Discussioncontrasting
confidence: 51%
“…Reversible cerebral vasoconstriction syndrome (RCVS) is a group of clinical entities characterized by prolonged, reversible vasoconstriction of the cerebral arteries that resolve within 3 months, associated with a rapid or gradual onset of severe headache, and complicated by other neurological symptoms (stroke, hemorrhage, encephalopathy, concomitant PRES, and seizures) in up to one-third of patients ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…A large adult case series showed that RCVS commonly affects middle-aged women [5,6]. In contrast, a review of pediatric RCVS patients reported a male predominance [2,7]. Brain computed tomographic angiography or MRA is useful for diagnosing RCVS.…”
mentioning
confidence: 99%
“…Brain computed tomographic angiography or MRA is useful for diagnosing RCVS. However, signs of vasoconstriction can be noticed 7 to 14 days after the onset of the headache [2,7]. Headache can precede the onset of brain angiography findings showing vasoconstriction, which causes difficulties in accurate diagnosis [2].…”
mentioning
confidence: 99%
See 1 more Smart Citation